EPCO-10. INTRATUMORAL HETEROGENEITY OF ENVIRONMENT-INDUCED EXPRESSION PROGRAMS IN GLIOMA PATIENTS AND DERIVED MODEL SYSTEMS. (12th November 2021) - Bayley, Nicholas; Tse, Christopher; Zhu, Henan; Ta, Lisa; Baufeld, Lynn; Gosa, Laura; Yan, Weihong; Prins, Robert; Yong, William; Cloughesy, Timothy; Liau, Linda; Graeber, Thomas; et al.
Abstract: Bulk tumor and single-cell RNA sequencing have revealed the remarkable molecular heterogeneity and plasticity of gliomas. This has led to the creation of tumor subtypes and cellular states describing inter- and intra-tumoral heterogeneity, respectively. While there has been great interest in creating and revising new classifications, the biological reasons for this degree of heterogeneity and the selective pressures driving it remain to be fully described. The brain tumor microenvironment (TME) is a complex, regionally heterogeneous ecosystem of communicating normal and malignant cell types and scavenge-able nutrients and metabolites. We hypothesized that distinct cellular interactions and metabolic flux in the TME may drive the inter- and intra-tumoral heterogeneity of gliomas. To identify tumorigenic programs impacted by environmental context we performed bulk RNA sequencing of over 35 triplets of patient glioma samples and their matched derivative models established in direct orthotopic mouse xenografts (DPDOX) and conventional gliomasphere cultures (GS). This analysis revealed environment-specific programs including in vivo immune and neuroglial signaling, in vitro lipid metabolism, and cell migration altered in model systems. These environmental programs are enriched in specific tumor subtypes and neuroglial signaling programs lost in vitro are dynamically upregulated upon re-transplantation in vivo . To further investigate associations between tumor cellular state and environment-driven programs we performed single-cell RNA sequencing of 3 patient and model system triplets. By annotating with brain cell atlases from previous single-cell characterizations, 6 major clusters and over 20 sub-clusters of tumor cell states and hybrid states were identified. Overlaying results from bulk sequencing revealed cell state-specific expression of environment-induced programs. Further, these cellular state "niches" diverge in model environments suggesting that environmental factors modulate not only the composition of cellular states but also their biological roles within gliomas.